HUBUNGAN KARAKTERISTIK SUBJEK, ASUPAN ZAT GIZI, DAN AKTIVITAS FISIK DENGAN KEKUATAN OTOT ANAK USIA SEKOLAH DI KABUPATEN PURWAKARTA - Lisnawati, Naintina; Haryanto, Irwan (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2017)
Background: Muscle strength is very important to do activities, not exception for school-aged children. It’s influenced by characteristics of the subject, nutrient intake, and physical activity. Objective: To analyze the correlation between subject’s characteristic, nutrient intake, and physical activity with muscle strength of school-age children in Purwakarta Regency. Method: This study used cross sectional design. Subjects of the study were the students of Junior High School 5 Purwakarta which amounted to 44 people. Muscle strength was measured using a Hand Dynamometer, lean body mass (LBM) using Bio Impedance Analysis (BIA), nutritional intake using a 2x24 hour Food Recall Form, and physical activity using a 24-hour Physical Activity Recall Form. Data analysis using Pearson Product Moment and Mann-Whitney Test. Result: Most of subjects' physical activity was mild (75%). There is no correlation between age (p = 0,228); gender (p = 0,102); LBM (p = 0.350); total energy (p = 0.770); carbohydrate intake (p = 0.968); protein (p = 0.663); sodium (p = 0.890); potassium (p = 0.737); calcium (p = 0.768); magnesium (p = 0,800); and physical activity (p = 0,682) with muscle strength of subjects. Conclusion: There is no correlation between subject’s characteristics, nutrient intake, and physical activity with muscle strength.